2020
DOI: 10.1080/14397595.2020.1812834
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of reduced-dose sulfamethoxazole-trimethoprim for chemoprophylaxis ofPneumocystispneumonia in patients with rheumatic diseases

Abstract: The efficacy and safety of reduced-dose sulfamethoxazole-trimethoprim for chemoprophylaxis ofPneumocystispneumonia in patients with rheumatic diseases 著者 Auther(s)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…The most commonly used prophylaxis scheme is trimethoprim/sulfamethoxazole (TMP-SMX) 480 mg/day (single-strength) or 960 mg three times a week; of note, there is some evidence that reduced doses (eg, half-strength, daily) may also be effective and associated with fewer adverse events 191–195. It should be noted that adverse events related to TMP-SMX (eg, nausea, headache, rash) are common, affecting about 20% of patients 196.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used prophylaxis scheme is trimethoprim/sulfamethoxazole (TMP-SMX) 480 mg/day (single-strength) or 960 mg three times a week; of note, there is some evidence that reduced doses (eg, half-strength, daily) may also be effective and associated with fewer adverse events 191–195. It should be noted that adverse events related to TMP-SMX (eg, nausea, headache, rash) are common, affecting about 20% of patients 196.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] The most commonly used prophylaxis scheme is trimethoprim/ sulfamethoxazole (TMP-SMX) 480 mg/day (single-strength) or 960 mg three times a week; of note, there is some evidence that reduced doses (eg, half-strength, daily) may also be effective and associated with fewer adverse events . [191][192][193][194][195] It should be noted that adverse events related to TMP-SMX (eg, nausea, headache, rash) are common, affecting about 20% of patients. 196 Concerns for higher adverse event rates have been expressed for individuals treated with methotrexate (in specific relation to the combination of TMP and MTX and the risk of cytopenia) or in patients with systemic lupus erythematosus (SLE).…”
Section: Recommendationmentioning
confidence: 99%
“…To establish an accurate indication for PJP prophylaxis, the safety of TMP/SMX, as well as its efficacy, needs to be thoroughly considered. Although previous studies reported cases of AEs caused by TMP/SMX, most of these studies did not assess AEs in a control group not receiving prophylaxis (25)(26)(27). Since assessing causality by reviewing medical records could be inaccurate, safety profiles of TMP/SMX that are extrapolated from ADRs could be biased.…”
Section: Discussionmentioning
confidence: 99%
“…Наиболее часто используемой схемой профилактики ППн является прием триметоприм/сульфаметоксазола (ТМП-СМК) 480 мг/сут. или 960 мг три раза в неделю [51,52]. Имеются публикации, свидетельствующие о том, что уменьшенные дозы (например, 240 мг ежедневно) также могут быть эффективными и связаны с меньшим количеством НЯ.…”
Section: пневмоцистная пневмонияunclassified